The Role of Pharmacists & Pharmacy Technician in Immunization: Strategies to Improve Vaccine Uptake - Khalid Salah Suwaylih al Rehaili,; Abdulaziz Mubarak Hussain Aljohani,; Mohammed Saaed Aljohany,; Adel Marzoq Albalawi,; Sami Dakhel A AL-Maghthawy,; Abdulkareem Dakhil Allah Salman Allehaibi,; Amin Hamoud Nassar Alsubhi,; Sahal Salem Alsehli, (International Journal of Medical Toxicology and Legal Medicine, 2024)
Introduction: Immunization remains one of the most effective public health strategies that have had remarkable impacts in decreasing incidence of infectious diseases and subsequently, mortality rate in worldwide. Consequently, the uptake of vaccines has remained low due to factors such as skepticism, difficult access to health services, and myths about vaccination. However, in fighting these problems, there is a growing role of the pharmacists and the pharmacy technicians. Aim of work: Tothe pivotal role of pharmacists and pharmacy technicians in immunization and the strategies they employ to improve vaccine uptake. Methods: We conducted a comprehensive search in the MEDLINE database's electronic literature using the following search terms: Role, Pharmacists, Pharmacy Technician, Immunization, Strategies, and Vaccine Uptake. The search was restricted to publications from 2016to 2024 in order to locate relevant content. We performed a search on Google Scholar to locate and examine academic papers that pertain to my subject matter. The selection of articles was impacted by certain criteria for inclusion. Results: The publications analyzed in this study encompassed from 2016 to 2024. The study was structured into various sections with specific headings in the discussion section. Conclusion: Immunization programs could not function without the support of pharmacists and pharmacy technicians, who are able to contribute a highly accessible, skilled and credible point of contact. In this manner, pharmacy professionals can play active roles in eliminating barriers to receiving vaccines and promoting population health literacy about vaccination, as well as engage in innovating approaches to enable those at risk of vaccine hesitancy to receive those vaccines they need. In the dynamic world of healthcare, the immunization activities of pharmacists and pharmacy technicians will therefore continue to grow. It is recommended that society begins to cultivate, train, and support them; and to include them in public health efforts in order to attain better coverage percentages within immunization and curb the infectious diseases from spreading. Pharmacy professionals have acknowledged roles in establishing a healthier and stronger world.